Relevance of health level 7 clinical document architecture and integrating the healthcare enterprise cross‐enterprise document sharing profile for managing chronic wounds in a telemedicine context. Issue 1 (23rd March 2016) - Finet, Philippe; Gibaud, Bernard; Dameron, Olivier; Le Bouquin Jeannès, Régine
Abstract : The number of patients with complications associated with chronic diseases increases with the ageing population. In particular, complex chronic wounds raise the re‐admission rate in hospitals. In this context, the implementation of a telemedicine application in Basse‐Normandie, France, contributes to reduce hospital stays and transport. This application requires a new collaboration among general practitioners, private duty nurses and the hospital staff. However, the main constraint mentioned by the users of this system is the lack of interoperability between the information system of this application and various partners' information systems. To improve medical data exchanges, the authors propose a new implementation based on the introduction of interoperable clinical documents and a digital document repository for managing the sharing of the documents between the telemedicine application users. They then show that this technical solution is suitable for any telemedicine application and any document sharing system in a healthcare facility or network.